Use the exponential equation:

\(\displaystyle{f{{\left({x}\right)}}}={a}{\left({1}+{r}\right)}^{{x}}\)

where aa is the initial value and rr is the growth rate/decay.

Given f(0)=4, then a=4. Since we are given a growth rate, then r=0.05: \(\displaystyle{f{{\left({x}\right)}}}={4}{\left({1}+{0.05}\right)}^{{x}}\)

\(\displaystyle{f{{\left({x}\right)}}}={4}{\left({1.05}\right)}^{{x}}\)

\(\displaystyle{f{{\left({x}\right)}}}={a}{\left({1}+{r}\right)}^{{x}}\)

where aa is the initial value and rr is the growth rate/decay.

Given f(0)=4, then a=4. Since we are given a growth rate, then r=0.05: \(\displaystyle{f{{\left({x}\right)}}}={4}{\left({1}+{0.05}\right)}^{{x}}\)

\(\displaystyle{f{{\left({x}\right)}}}={4}{\left({1.05}\right)}^{{x}}\)